Is there any clinical or laboratory predictive factor for cetuximab-induced skin toxicity?. Issue 5 (4th May 2021) - Acikgoz, Yusuf; Bal, Oznur; Ucar, Gokhan; Durnali, Ayse; Ergun, Yakup; Dirikoc, Merve; Esen, Selin Akturk; Dogan, Mutlu
ABSTRACT: BACKGROUND : We aim to explore the predictive role of clinical and hematological parameters for cetuximab-induced skin toxicity (CI-ST) and survival outcomes in patients according to risk categories. RESEARCH DESIGN AND METHODS : The optimal cut-off values for hematological parameters were assessed by the Receiver Operating Characteristic (ROC) analysis. Patients were classified as High risk, Intermediate risk and Low risk subgroups with respect to platelet to lymphocyte ratio (PLR) and red blood cell count (RBC) values. Kaplan-Meier test was used for survival analysis, and outcomes were analyzed by Log-rank test. P-value <0.05 considered as statistically significant. RESULTS : Among hematological parameters, only PLR and RBC were statistically significant prognostic factors.Optimal cut-off value for PLR was 196.2 (82.9% sensitivity and 61.1% specificity), and 4.610x106/µL for RBC count (65.9% sensitivity and 81.1% specificity). Patients in high risk group had increased risk with an OR:69.34 (p<0.0001), and in the intermediate risk group had an OR:28.73 (p=0.002) for CI-ST. De novo metastatic patients had 9.11-fold increased risk for CI-ST compared to recurrent metastatic patients (p=0.028). CONCLUSION : Our study indicates that risk categories based on PLR and RBC can predict CI-ST and de novo metastatic patients had higher risk for CI-ST.